UPAH PERSPEKTIF ISLAM DALAM PENGEMBANGAN EKONOMI - Urrahmah, Nida; Yono, Yono; Amelia, Amie (ISTISMAR, 2024)
Religion as a from of belief is part and core of the existing set of values and becomes culture or costums in society.Religion is a series of plans for behavior based on values and rules.Economics is used to study human behavior in using scarce resources to produce goods and services that humans need.The relationship and position between the development of religion and rising economic standards is very relevant,the relationship can also influence each other. The problem in paying wages is the perspective of enterpreneurs and the government towards workers who only use it as a means of production, capacity and attracting investment.For enterpreneurs, wages are part of production costs,so expenses must be calculated as economically as possible and their use maximized to increase productivity and work ethic. In fact, for workers, wages are very useful income to meet their needs. This is based on Marshall's theory that setting a minimum wage allows workers to improve their nutrition so that in the long term they can increase their productivity. Meanwhile, wage determination in Islam is based on work services us usefulness and benefits of a person's energy and based on the burden in life .